2007
DOI: 10.1182/blood-2007-02-075366
|View full text |Cite
|
Sign up to set email alerts
|

The p110delta catalytic isoform of PI3K is a key player in NK-cell development and cytokine secretion

Abstract: The signal transduction pathways that lead activated natural killer (NK) cells to produce cytokines, releases cytotoxic granules, or do both, are not clearly dissected. For example, phosphoinositide 3-kinases (PI3Ks) are key players in the execution of both functions, but the relative contribution of each isoform is unknown. We show here that the catalytic isoform p110␦, not p110␥, was required for interferon-␥ (IFN-␥), tumor necrosis factor-␣ (TNF-␣), and granulocyte macrophage colony-stimulating factor (GM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
84
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 44 publications
6
84
1
Order By: Relevance
“…It was suggested that NK cell-mediated cytotoxicity might be downregulated by G-CSF through the PI3K/Akt and ERK/MAPK signaling molecules, and the PI3K/Akt signaling then decreased expression of cytotoxicity-related molecules, TPI, while the ERK/MAPK signaling may be involved in regulation of other genes, such as cellular adhesion, polarity, development, cytokine production and granule secretion. 27,28 Recently, clinicians have begun to use new agents such as plerixafor (AMD3100) to optimize the mobilization of HSC before transplantation for treatment of hematologic diseases and inborn errors of metabolism. 23,36 Our results may provide additional important information regarding regulation of NK cell activity for developers of potential drugs for advanced stem cell mobilization in HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that NK cell-mediated cytotoxicity might be downregulated by G-CSF through the PI3K/Akt and ERK/MAPK signaling molecules, and the PI3K/Akt signaling then decreased expression of cytotoxicity-related molecules, TPI, while the ERK/MAPK signaling may be involved in regulation of other genes, such as cellular adhesion, polarity, development, cytokine production and granule secretion. 27,28 Recently, clinicians have begun to use new agents such as plerixafor (AMD3100) to optimize the mobilization of HSC before transplantation for treatment of hematologic diseases and inborn errors of metabolism. 23,36 Our results may provide additional important information regarding regulation of NK cell activity for developers of potential drugs for advanced stem cell mobilization in HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Articles have reported that PI3K links NKG2D-activated signaling pathway in NK cells with cellular adhesion, polarity, development, and cytokine and granule secretion, 27,28 implying that inhibition of the PI3K/Akt The relative values were normalized to the internal glyceraldehyde-3-phosphate dehydrogenase control and were calculated from at least three independent experiments. All results were expressed as mean±s.d.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that PI3Kd activity regulates post-Golgi transport and secretion of TNF in macrophages 18,19 . PI3Kd is similarly implicated in the release of cytokines from other immune cells [20][21][22][23][24] , and PI3Kd-selective inhibitors have significant anti-inflammatory efficacy [24][25][26] . A dual PI3Kg/d inhibitor has been shown to reduce damage in myocardial infarction 27 .…”
mentioning
confidence: 99%
“…In contrast to the ubiquitous expression of PI3K p110a and p110b, the p110d subunit is predominantly found in hematopoietic cells. Besides its fundamental roles in B cell development and functions (25), p110d is implicated as a central regulator of intracellular vesicle trafficking associated with inflammatory cytokine responses in different immune cells such as mast cells (26), NK cells (27), B cells (28,29), and T cells (30). In macrophages, p110d was required for fission of TNF-containing vesicles from the Golgi apparatus and transport to the cell surface upon stimulation with the TLR4 agonist LPS (31).…”
mentioning
confidence: 99%